Health education for fall prevention in elderly inpatients with orthostatic hypotension: a single-center controlled intervention study in Nantong city - Haiyan SHEN; Jinyan HUANG; Yuchen MA; Xiangyun QIAN (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo evaluate the impact of a health education intervention based on the protection motivation theory (PMT) on the prevention of falls in elderly hospitalized patients with orthostatic hypotension (OH). Methods A total of 400 elderly OH patients aged ≥ 65 years admitted to a tertiary grade A hospital in Nantong city from January 2019 to December 2022 were divided into an intervention group (n = 199) and a control group (n = 201). The control group received routine health education on fall prevention, while the intervention group received an additional health education intervention program based on PMT. The 36-Item Short Form Health Survey (SF-36), the Fall Risk Assessment Scale for the Elderly, and the Balance Test Scale for the Elderly were used to collect information on the two groups' fall risk, balance ability, and quality of life scores of before and 6 months after the intervention. Results The mean age of the 400 patients was 66.53 ± 7.51 years. There were no statistically significant differences in age, sex, education level, occupation, marital status, and monthly income between the intervention and control groups (all P > 0.05). Before the intervention, there were no statistically significant differences in balance test, fall risk assessment and SF-36 scores between the two groups (all P > 0.05). After 6 months of intervention, except for the health change dimension, the SF-36 scores of the intervention group were higher than those of the control group; the balance ability and fall risk scores of the intervention group were lower than those of the control group, and the differences were statistically significant (all P < 0.05). ConclusionThe PMT-based fall prevention health education intervention program can help reduce the risk of falls, improve balance, and improve the quality of life of elderly patients with OH.